Co-culture of outgrowth endothelial cells with human mesenchymal stem cells in silk fibroin hydrogels promotes angiogenesis8Affiliations 1 and 3 contributed equally. (7th June 2016) - Sun, Wei; Motta, Antonella; Shi, Yang; Seekamp, Andreas; Schmidt, Harald; Gorb, Stanislav N; Migliaresi, Claudio; Fuchs, Sabine
Abstract: Sufficient vascularization of the implant construct is required for tissue regeneration to ensure the supply of oxygen and nutrients. In our previous work, we established sonication-induced silk fibroin hydrogel to load neural stem cells for brain tissue engineering applications. In this study, we explored the application of silk fibroin as an injectable hydrogel for vascularization of soft tissues. We investigated the ability of outgrowth endothelial cells (OECs) in mono-culture or in co-culture with human bone marrow-derived mesenchymal stem cells (BM-MSCs) to form capillary networks in silk fibroin hydrogels. Furthermore, the silk fibroin hydrogel was modified with IKVAV peptide revealing a sequence derived from the extracellular matrix component laminin-1 to test its effects on angiogenesis, using unmodified and VVIAK modified silk fibroin hydrogel as controls. In monocultures of OECs, no angiogenic structures were observed in silk fibroin hydrogels. In contrast, vascular structures were abundant and increased in co-culture, as confirmed by immunocytochemistry and scanning electron microscopy (SEM) over 10 d of culture in silk fibroin-based hydrogels. Although no significant differences in angiogenic activity seem to be caused by the IKVAV peptide in our experimental settings, these results indicate that sonication-induced silk fibroin-based hydrogels support the formation of functional endothelial tubes and vascularization networks in the presence of mesenchymal cells supporting the vascular sprouting of endothelial cells.